Health monitoring by functional indicators with the help of sensors at the phase of patient rehabilitation in today's conditions - Buhaienko, Tetiana; Popovych, Dariya; Bondarchyk, Valentyna; Novakova, Lyubov; Hevko, Ulіana; Vayda, Olena; Myndziv, Kateryna (Journal of Education, Health and Sport, 2022)
Nowadays, people's need for fast and effective rehabilitation processes is growing significantly. Sensory devices are available for people with functional disabilities, which are used for rehabilitation to help a person's health and return to an appropriate standard of living. Scientists in the field of rehabilitation medicine are actively studying the method of remote monitoring of the physiological indicators of the human body. The last decade has been marked by the intensive development of research in the field of sensor devices. For example, mechanical, robotic systems and exoskeletons, which enable people with limited physical capabilities to move their bodies, occupy an important place among the technical means for restoring the condition of the human locomotor system. Despite the existence of various technical systems and means for rehabilitation after injuries and diseases of the spine and lower limbs, the latest modern exoskeletons of various types have not yet been used.